2012
DOI: 10.1371/journal.pone.0036245
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Adjuvants Potentiate T Cell-Mediated Immunity Induced by a NY-ESO-1 Based Antitumor Vaccine

Abstract: Immunological adjuvants that induce T cell-mediate immunity (TCMI) with the least side effects are needed for the development of human vaccines. Glycoinositolphospholipids (GIPL) and CpGs oligodeoxynucleotides (CpG ODNs) derived from the protozoa parasite Trypanosoma cruzi induce potent pro-inflammatory reaction through activation of Toll-Like Receptor (TLR)4 and TLR9, respectively. Here, using mouse models, we tested the T. cruzi derived TLR agonists as immunological adjuvants in an antitumor vaccine. For com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 55 publications
(88 reference statements)
0
31
0
Order By: Relevance
“…46 The use of T. cruzi-derived TLR agonists as immunological adjuvants also resulted in a significant delay in the growth of the B16-F10 melanoma cell line expressing NY-ESO-1 antigen. 47 Interestingly, protective immunity correlated with the magnitude of CD8 1 T-cell responses induced by a specific TLR agonist. One of the major challenges in the development of an efficient anticancer vaccine is overcoming immune tolerance to tumor-associated antigens (TAA), as well as the active immune evasion strategies developed by tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 The use of T. cruzi-derived TLR agonists as immunological adjuvants also resulted in a significant delay in the growth of the B16-F10 melanoma cell line expressing NY-ESO-1 antigen. 47 Interestingly, protective immunity correlated with the magnitude of CD8 1 T-cell responses induced by a specific TLR agonist. One of the major challenges in the development of an efficient anticancer vaccine is overcoming immune tolerance to tumor-associated antigens (TAA), as well as the active immune evasion strategies developed by tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it was found that a recombinant nonpathogenic clone of T. cruzi expressing a cancer testis antigen (NY‐ESO‐1) induces antigen‐specific T‐cell responses and effective protection against tumors in a mouse model . The use of T. cruzi ‐derived TLR agonists as immunological adjuvants also resulted in a significant delay in the growth of the B16‐F10 melanoma cell line expressing NY‐ESO‐1 antigen . Interestingly, protective immunity correlated with the magnitude of CD8 + T‐cell responses induced by a specific TLR agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its role in activating the immune response, GPI mucins and GIPLs are being used as adjuvants in immunization protocols against T. cruzi, with the hope of finding effective vaccines [54]. Because of its role in activating the immune response, GPI mucins and GIPLs are being used as adjuvants in immunization protocols against T. cruzi, with the hope of finding effective vaccines [54].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Junqueira et al (2012) used a melanoma mouse models to investigate the role of antigens derived of plasmatic membrane of the Trypanosoma cruzi as immunological adjuvants in an antitumor vaccine. Obtaining favorable results, the antigens of Trypanosoma cruzi were considered an efficient immunological adjuvant.…”
Section: Vaccinesmentioning
confidence: 99%